BIKAMERALISME SETEGAH HATI - iqbal aidar idrus (JURNAL POLINTER : KAJIAN POLITIK DAN HUBUNGAN INTERNASIONAL, 2017)
On a bicameral system the DPR and DPD positions should be balanced so that checks and balances to be built can be effective. But unfortunately, the presence of DPD in Indonesian state administration is still considered halfhearted. This is evident from some of his very limited authorities and has absolutely no authority to disconnect except for suggestions, judgments and suggestions. In fact, the legitimacy of DPD is not inferior to DPR members even the requirement to become DPD member candidates should collect 1000 to 5000 signatures and they directly face the people, in contrast to the DPR elected through political parties. This paper looks at how the MPR's relationship with the DPR and DPD is not in the institutional function but is seen from the composition of MPR members consisting of members of DPR and DPD, while the relationship between DPR and DPD is viewed from the institutional function, namely DPD is an institution of consideration or support for the House of Representatives Legislation, consideration, and supervision. The actual parliamentary institution is in the House because it has the functions of legislation, budgetary function and oversight function, and even has a function to give consideration / approval. In carrying out its function, the DPR is given the right of interpellation, right of inquiry and right of opinion. The position of the House becomes very strong because it cannot be frozen or dissolved by the President, thus DPD has a role that is not maximal in performing the functions of check and balances perfectly, Because they do not have veto rights over the bill and are only entitled to propose certain laws only, and the function of consideration and supervision is very dependent and rely on other parties, especially the House and the President.